THE EFFECT OF DEBT LEVELS, CASH FLOW VOLATILITY, AND AMOUNT OF ACCRUALS ON PROFIT PERSISTENCE IN COMPANIES MANUFACTURING SUB-SECTORS OF VARIOUS INDUSTRIES LISTED ON INDONESIA STOCK EXCHANGE YEAR 2017-2021 - Simanjuntak, Arthur; Mesakh, Januardi; Ginting, Mitha C.; Rajagukguk, Eva Gloria (Universitas Methodist Indonesia, 2023)
This research was conducted to see how much influence the Level of Debt, Cash Flow Volatility, and Amount of Accruals have on Profit Persistence in Manufacturing Companies in the Various Industries Sub Sector in 2017-2021. The population in this study is the 2017-2021 Financial Statements for 9 Manufacturing Companies in Various Industrial Sub-Sectors, so the total sample is 45. This type of research uses a descriptive quantitative method with secondary data so that it can describe each variable in this study. The data will be processed using Statistical Product and Service Solution (SPSS) Version 25. The data analysis technique in this study uses descriptive analysis test, classic assumption test, coefficient of determination test, multiple linear regression analysis test, and uses a partial hypothesis test (t test ) and simultaneous test (F test) with a significance level of 0.05 . Based on the results of data analysis tests that have partially Debt Level has a negative and significant effect on Profit Persistence and Cash Flow Volatility has a negative but not significant effect, while the Accrual Amount has a positive and significant effect on Earnings Persistence., and the results of the study simultaneously stated that all independent variables significant effect on Profit Persistence simultaneously with the test results of the coefficient of determination showing an effect of 33.5%.